Medication persistence to antihypertensive drug treatment – a cross-sectional study of attitudes towards hypertension and medication in persistent and non-persistent patients. (3rd September 2019) - Qvarnström, Miriam; Kahan, Thomas; Kieler, Helle; Brandt, Lena; Hasselström, Jan; Wettermark, Björn
Abstract: Purpose: To study the differences in attitudes towards hypertension and drug treatment between patients persistent and non-persistent to antihypertensive drug treatment. Materials and methods: Cross-sectional study on patients with hypertension treated at 25 primary healthcare centres in Stockholm, Sweden. Questionnaires were sent to the patients 3–12 months after initiation of antihypertensive drug treatment. Persistent medication users, defined as patients with less than 30 days without tablet supply between prescription refills, were compared with non-persistent users by scores from Likert scales: Brief-Illness Perception Questionnaire (Brief IPQ, 0–10) and Beliefs about Medicines Questionnaire (BMQ General, 4–20 and BMQ Specific, 5–25). Results: A total of 711 patients were included in the final analyses (mean age: 62 years; 50% women), of whom 609 (86%) were classified as persistent and 102 (14%) as non-persistent by analyses of their filled prescriptions. Likert scales from the Brief-IPQ showed (all p < 0.02) that persistent patients believed that hypertension was a chronic condition (median 6 vs. 4), that hypertension had less consequences on their life (median 2 vs. 3) and that they can prevent cardiovascular disease by taking antihypertensive treatment (median 7 vs. 5). Likert scales from the BMQ General showed (all p < 0.02) that persistent patients believed that there are potential benefits from taking the treatment (median 16 vs. 16), and they did not believe that the doctors put too much trust in drugs (median 12 vs. 13). Further, results from the BMQ Specific showed that they believed that the antihypertensive drugs are necessary for them in order to maintain or improve their own health (median 17 vs. 16). Conclusions: Primary healthcare providers should further emphasize the chronicity of hypertension diagnosis and the benefits of treatment, to improve the patients' medication persistence to antihypertensive treatment.